Clusters in the Function of Innovative Activities and Competitiveness of Enterprises - Stefanović, Suzana; Dukić, Ana; Milanović, Marina (Industrija, 2015)
Development and diffusion of innovations in order to achieve competitive advantage of enterprises is one of the key reasons of forming clusters in the contemporary business. The paper emphasizes the importance of clusters for strengthening innovativeness of enterprises, as well as the significance of clusters for the economic development of the regions/countries in which they exist. The paper will attach special significance to the importance of clusters for strengthening innovativeness and competitiveness of the Serbian economy. The Serbian Automotive Cluster will be discussed in detail. Clusters enable Serbian enterprises to remove constraining factors of their growth through cooperation. The presented data in the paper show that the enterprises increased their innovative activities when they joined the cluster, which also affected the increase of the enterprises’ income after launching new and modified products.